Detection of after-discharges during intraoperative functional brain mapping in awake brain tumor surgery using a novel high-density circular grid. Issue 4 (April 2020) - Tatum, William O.; McKay, Jake H.; ReFaey, Karim; Feyissa, Anteneh M.; Ryan, Dan; Ritaccio, Anthony; Middlebrooks, Erik; Yelvington, Kirsten; Roth, Grayson; Acton, Emily; Grewal, Sanjeet; Chaichana, Kaisorn; et al.
Highlights: Strip electrodes are limited to record electrical-discharges during awake craniotomy. The 360° electrode array provides a non-inferior temporal-spatial recording dynamic. After-discharge differentiation may improve our understanding of brain tumor related seizure neurobiology. Abstract: Objective: To evaluate intraoperative use of a novel high-density circular grid in detecting after-discharges (AD) on electrocorticography (ECoG) during functional brain mapping (FBM). Methods: FBM during glioma surgery (10/2016 to 5/2019) recorded ADs using a 22-channel circular grid compared to conventional strip electrodes. ADs were analyzed for detection, duration, amplitude, morphology, histology, direction, and clinical signs. Results: Thirty-two patients (mean age 54.2 years; r = 30–75) with glioma (WHO grade II-IV; 20 grade IV) had surgery. ADs during FBM were more likely in patients with wild-type as opposed to IDH-1 mutants (p < 0.0001) using more contacts compared with linear strip electrodes (p = 0.0001). More sensors tended to be involved in ADs detected by the circular grid vs strips (6.61 vs 3.43; p = 0.16) at lower stimulus intensity (3.14 mA vs 4.13 mA; p = 0.09). No difference in the number of cortical stimulations before resection was present (38.9 mA vs 47.9 mA; p = 0.26). ADs longer than 10 seconds were 32.5 seconds (circular grid) vs 58.4 (strips) (p = 0.12). Conclusions: High-density circular grids detect ADs in 360 degrees during FBM for glioma resection. Provocation of ADs was more likely in patients with wild-type than IDH-1 mutation. Significance: Circular grids offer high-resolution ECoG during intraoperative FBM for detection of ADs.